Incorporation of transuranium elements: coordination of Cm(iii) to human serum transferrin. Issue 41 (1st October 2018) - Adam, Nicole; Trumm, Michael; Smith, Val C.; MacGillivray, Ross T. A.; Panak, Petra J.
Abstract : Structure determination of Cm(iii )-transferrin by a combined spectroscopic and theoretical approach gives insight into the biochemical behaviour of incorporated actinides. Abstract : The coordination environment of Cm(iii ) bound at the Fe(iii ) binding sites of transferrin was investigated using a combined experimental and theoretical approach. Complexation studies with two hTf/2N single point mutants, Y95F (Tyr → Phe) and H249A (His → Ala) were performed. The substitution of Tyr 95 by the non-complexing Phe prevents Cm(iii ) from forming of a strong, multidentate complex with the mutant. In contrast, with the H249A mutant Cm(iii ) complexation at the binding site still occurs although a slightly higher pH is required to form the complex. This elucidates that His plays a minor role and is not a key ligand like Tyr 95. MD/DFT calculations of Cm(iii ) bound at the N-terminal binding site provide further structural information. All coordinating groups present in the Fe(iii ) transferrin complex are also found for Cm(iii ), i.e. Asp 63, Tyr 95, Tyr 188 and His 249. Additionally, two water molecules, one monodentate and one bidentate carbonate ion complete the coordination environment. This structure of the Cm(iii ) hTf/2N complex is confirmed by vibronic sideband spectroscopy which allows an identification of the directly coordinating groups. The results underline an involvement of Asp 63, Tyr 95, Tyr 188 and His 249 as well as carbonate in Cm(iii ) coordination at the transferrin Fe(iii ) binding site.